(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Understanding the effect of population and unemployment rate on Indonesia’s economic growth during the COVID-19 pandemic period is the main focus of this study. Through descriptive and explanatory approaches as well as multiple linear regression analysis, the study highlights that population increase has a positive impact on economic growth, while the unemployment rate has a negative influence. These findings confirm that economic growth can be spurred by population growth, but can be hampered by high unemployment. In addition, factors such as the quality of human resources, infrastructure, and government policies also influence the dynamics of economic growth. Therefore, it is important for the government to continue to improve these aspects in order to optimize Indonesia’s economic potential. This study provides a deep understanding of the relationship between demographic factors and economic growth during the COVID-19 pandemic.